Reducing Cognitive Bias of Pre-Service History Teachers through Augmented Reality - Elfa Michellia Karima; Nurlizawati Nurlizawati; Firza Firza; Nur Fatah Abidin; Yusuf Ibrahim (JOIV : International Journal on Informatics Visualization, 2024)
Cognitive biases can be problematic and dangerous in history learning. This study aimed to identify the extent to which the independent variables of the case study method and augmented reality influence the dependent variables, as well as evaluate the strength and direction of the relationship between these variables in reducing the cognitive biases of pre-service history teachers. The method used is multiple linear regression to identify the extent to which the application of the case method and the use of augmented reality in learning affect the dependent variable under study. The results showed that augmented reality contributed to the understanding of the history of prospective pre-service history teachers more than the case study method. The effect of the case study method was 7.6% on historical knowledge, and augmented reality media had a 13.9% effect on historical experience. Lecturers can use augmented reality in learning for prospective pre-service history teachers to increase student understanding of history learning material and reduce cognitive biases. This research has implications for using technology and digitalization in history learning for prospective pre-service history teachers to understand history, conceptions, and past events and reduce bias. Understanding history is essential for prospective pre-service history teachers. Prospective pre-service history teachers must also understand a historical event broadly and from various perspectives. Technology-based learning in history learning is one of the right ways to avoid cognitive bias.